ANALISIS KESALAHAN PENULISAN PADA SEBUAH PANTUN DALAM BAHAN AJAR SENI BUDAYA MELAYU TINGKAT SEKOLAH DASAR KELAS 5 DI KEPULAUAN RIAU - Fitri Alaminanda; Melya Nurjanah; Tiara Yuyun; Hasnah Faizah (JISPENDIORA Jurnal Ilmu Sosial Pendidikan Dan Humaniora, 2022)
Writing Arabic Malay is a skill that has its own rules. In addition, Arabic-Malay writing has a dynamic nature, so that each of these rules also changes. In one of the elementary schools in the Riau Archipelago, one of them in the 5th grade Cultural Arts subject there is pantun material which is written in Arabic Malay. In this material, students are required to be able to master writing skills as well as reading skills in Arabic Malay in the pantun material. Of course, in order for student learning outcomes to achieve good results, the learning material must be in a correct and appropriate condition. In this study, a descriptive qualitative method was used which explained how an error occurred in one of the rhymes in the 5th grade cultural arts teaching materials which were conducted from October to November 2022. Meanwhile, this research resulted in the fact that there were several errors in the writing of the rhyme on the cultural arts teaching materials writing material. Malay Arabic rhymes.